Nowe źródła do badań północnych obszarów Polski, należących do byłych Prus Wschodnich - Szcześniak, Krystyna (Nazwy terenowe i miejscowe w przestrzeni fizycznej, 2016)
The article discusses the work of German historian Wolfgang Rothe which is valuable for onomastic research regarding the Protestant parishes in the area of the former East Prussia (now the area of the parishes lies partly in Poland and partly in Russia). Born in the family of Salzburg settlers, the laureate of Gołdap prize “Romincki Lynx” with the help of former residents of these areas, and with his work he collected seven volumes (the eighth one in preparation) of very reliable and extensive historical documentation (including onomastic ones: records of names of settlements taken from different documents, settlements list of family names, first names and occupations of inhabitants up to year 1938). Wolfgang Rothe documented also the reality of that time on maps, photographs and plans of the various villages and settlements, supplementing those with the memories of former residents of respective parishes and glossary of interesting lexemes and phrasemes. This material allows filling a number of history white spots (the history of toponymy and anthroponymy) of the area.